Waveform-Encoded SAR: A Novel Concept for Nadir Echo and Range Ambiguity Suppression - Villano, Michelangelo; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2018)
Synthetic aperture radar (SAR) remote sensing allows high-resolution imaging independent of weather conditions and sunlight illumination and is therefore very attractive for the systematic observation of dynamic processes on the Earth's surface. As a consequence of the pulsed operation of SAR, however, nadir echoes and range ambiguities may significantly affect the SAR image quality, if the pulse repetition frequency (PRF) is not conveniently constrained in the design of spaceborne SAR systems. As these constrains typically limit both the swath width and the ambiguity performance of the SAR system, the investigation of novel concepts for nadir echo and range ambiguity suppression is of great interest. Waveform-encoded SAR allows suppression (not only smearing) of the nadir echoes and range ambiguities by means of waveform diversity on transmit and multi-focus post-processing. This technique yields improved image quality and increased flexibility in the design of novel SAR systems.
Keywords: SAR.